Spatial Analysis of Disaster Vulnerability in Wonolelo, Magelang Regency - Arif, Nursida; Martiana, Aris; Hadi, Bambang Syaeful; Surjati, Endang; Widodo, Edi; Zanyc, Yuinta Diaz Aprilia; Akhmad, Afandi; Fathoni, Muhammad Rizal (UNIVERSITY OF LAMPUNG, 2025)
This research aims to assess the level of disaster vulnerability in the Wonolelo tourist village area using spatial analysis with an overlay method of several factors causing disaster vulnerability. The location of Wonolelo Village on the slopes of Mount Merapi with a rather steep to steep topography makes Wonolelo Village very vulnerable to landslides and the eruption of Mount Merapi. The research results show that Wonolelo Village has a high vulnerability to volcanic disasters (63.71%) and medium vulnerability to landslides (99.12%). The findings of this research can be used to inform disaster mitigation policies and strategies in Wonolelo Village and other vulnerable areas.